PREVALENSI GINGIVITIS PADA IBU HAMIL BERDASARKAN USIA KEHAMILAN, PEKERJAAN, DAN PENDIDIKAN DI RSUD KLUNGKUNG TAHUN 2017 - Komang Eni Pradnyanaputri; Sari Kusumadewi; Desak Nyoman Ari Susanti (Odonto : Dental Journal, 2018)
Background: Pregnant women usually suﬀer from gingivitis due to an increasein progesterone and estrogen hormones followed by hypervascularization. As the result, gingiva becomes more sensitive to plaque and calculus. Pregnant women in Trimester II began to experience gingivitis and would get worse in the trimester III. As known, gingivitis in pregnant women may be aﬀected by age of pregnancy, occupation and education level. The aim of the study was to describethe prevalence of gingivitis in pregnant women at RSUD Klungkung, related toage of pregnancy, occupation and education.Methods: This research was a descriptive study using cross sectional study approach. Sample in this study was 85 people using consecutive sampling technique. Data collection was done by giving questionnaire and screening to pregnant women to know their gingival score.Result: The results of this study showed that most of pregnant women in trimester I experienced gingivitis score 1 (57,9%), trimester II gingivitis score 2 (65,5%), and trimester III gingivitis score 3 (83,8%). Pregnant women who didnot work had more gingivitis (42%) than pregnant women who worked (37.1%).Pregnant women with lower education level experienced more gingivitis (92.8%) than pregnant women with higher education level (75%).Conclusion: The number of gingivitis in pregnant women is increasing astheir age of pregnancy, where the ginggivitis score in trimester I is better than trimester III. This result also correlated with age of pregnancy, occupation andeducationlevel.